Inflammation-mediated muscle metabolic dysregulation local and remote to the site of major abdominal surgery - Varadhan, Kristina K.; Constantin-Teodosiu, Dumitru; Constantin, Despina; Greenhaff, Paul L.; Lobo, Dileep N. (Elsevier, 2017)
Background & aims: Postoperative hyperglycaemia is common in patients having major surgery and is associated with adverse outcomes. This study aimed to determine whether bacteraemia contributed to postoperative systemic inflammation, and whether increases in the expression of muscle mRNAs and proteins reflecting increased muscle inflammation, atrophy and impaired carbohydrate oxidation were evident at the time of surgery, and both local and distant to the site of trauma, and could be associated with impaired glucoregulation. Methods: Fifteen adult patients without diabetes undergoing major abdominal surgery participated in this observational study set in a university teaching hospital. Arterialised-venous blood samples and muscle biopsies were obtained before and after major elective abdominal surgery, from sites local (rectus abdominis e RA) and remote to the site of surgery (vastus lateralis e VL). The main outcome measures included blood glucose concentrations, gut permeability and changes in expression of muscle mRNAs and proteins linked to inflammation and glucose regulation. Results: Immediately postoperatively, RA demonstrated markedly increased mRNA expression levels of cathepsin-L (7.5-fold, P < 0.05), FOXO1 (10.5-fold, P < 0.05), MAFbx (11.5-fold, P < 0.01), PDK4 (7.8-fold, P < 0.05), TNF-a (16.5-fold, P < 0.05) and IL-6 (1058-fold, P < 0.001). A similar, albeit blunted, response was observed in VL. Surgery also increased expression of proteins linked to inflammation (IL-6; 6-fold, P < 0.01), protein degradation (MAFbx; 4.5-fold, P < 0.5), and blunted carbohydrate oxidation (PDK4; 4-fold, P < 0.05) in RA but not VL. Increased systemic inflammation (TNF-a, P < 0.05; IL-6, P < 0.001), and impaired postoperative glucose tolerance (P < 0.001), but not bacteraemia (although gut permeability was increased significantly, P < 0.05) or increased plasma cortisol, were noted 48 h postoperatively. Conclusions: A systemic postoperative proinflammatory response was accompanied by muscle inflammation and metabolic dysregulation both local and remote to the site of surgery, and was not accompanied by bacteraemia.